A short stereoselective total synthesis of the fusarium toxin equisetin. - Burke, LT; Dixon, D; Ley, S; Rodríguez, F (2000)
A short stereoselective synthesis of the fusarium toxin equisetin, an N-methylserine-derived acyl tetramic acid and potent inhibitor of HIV-1 integrase enzyme, is described using as the key step a stereoselective lithium perchlorate mediated intramolecular Diels-Alder reaction of a fully conjugated E,E,E-triene with a trisubstituted gamma,delta-unsaturated beta-ketothioester.